From Green Banking Disclosure to Firm Value: Evidence on the Mediating Role of Bank Soundness - Vina Yunistiyani; Alfiyah Aditya Rahmawati; Zakia Maulida Antono (CV Edujavare Publishing, 2026)
Green banking disclosure has become an important component of sustainable banking practices and is expected to provide positive signals to stakeholders regarding a bank’s environmental commitment and long-term performance. This study aims to examine the role of bank soundness in mediating the relationship between green banking disclosure (GBD) and firm value (FV). A quantitative approach was employed using data from all banks listed on the Indonesia Stock Exchange during 2019–2024. Data were collected from Bloomberg and the Indonesia Stock Exchange website. Using purposive sampling, 144 firm-year observations from 24 banks were selected and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with WarpPLS 8.0. The findings indicate that GBD has no direct effect on FV but has a positive effect on bank soundness. In addition, bank soundness positively affects FV and successfully mediates the relationship between GBD and FV. These results suggest that the contribution of GBD to firm value is realized indirectly through improvements in bank soundness. This study provides the first empirical evidence on the mediating role of bank soundness in the GBD–FV relationship and contributes to signaling theory by demonstrating the importance of sustainability-related information in stakeholders’ fund placement decisions. Furthermore, bank core capital is incorporated as a control variable to capture banks’ readiness to implement sustainability-related policies.